From Visual To Understanding: Analysis Of The Effect Of Canva Learning Media On Phbs Motivation - Hasanah Aprilia, Niswatin; Prihanto, Junaidi Budi; Ridwan, Mochamad (Jurnal Pendidikan Jasmani (JPJ), 2025)
Low learning motivation in understanding Clean and Healthy Living Behavior (PHBS) material is still problematic at the elementary school level. Lack of student awareness of healthy behaviors such as washing hands and choosing nutritious foods indicates the need for innovation in learning strategies. This study aims to analyze the effect of Canva-based video media on student learning motivation on the PHBS topic. The study used a quantitative method with a one-group pretest-posttest quasi-experimental design. The research subjects consisted of 19 fourth-grade students at SD Negeri 2 Pule. The research instrument was a motivation questionnaire given before and after treatment. The results of the hypothesis test showed a significance value of 0.000 <0.05, it can be concluded that there was a significant effect after being given treatment with the use of Canva videos on increasing learning motivation. Therefore, Canva media can be used as an alternative technology-based learning that is effective in increasing motivation, especially in PHBS material.